Pengabdian kepada Masyarakat melalui Kuliah Kerja Nyata (KKN) di Desa Buddagan Kabupaten Pamekasan - Mochamad Reza Adiyanto; M. Bagas Adi Saputra; Cindy Mildawati Virgina Putri; Nadaa Avria Hanum; Marta Margareta Dubri (Lembaga Pengembangan Kinerja Dosen, 2026)
Community Service Program (KKN) is an implementation of the Tridharma of Higher Education aimed at dedicating knowledge and technology to society. This article analyzes the implementation of the KKN program by students of Universitas Trunodjoyo Madura Group 30 in Buddagan Village, Pademawu District, Pamekasan Regency, focusing on community empowerment through aspects of environment, education, entrepreneurship, and village digitalization. The activities were carried out using a participatory approach with observation techniques, interviews, and discussions with the community and village stakeholders. The flagship programs include the socialization of used cooking oil for making aromatherapy candles, installation of environmental education plaques, anti-bullying socialization at SDN Buddagan 2, and the creation of the official social media for Buddagan Village. The results show an increase in community awareness, especially among PKK mothers, regarding the health and environmental dangers of used cooking oil and the potential for a creative economy based on domestic waste. The anti-bullying program successfully instilled empathy and mutual respect values in students, while the village digitalization strengthened public access to information and a positive village image. The KKN program in Buddagan Village has had a positive impact on social behavior changes in the community and serves as a model for sustainable community service.